(untitled) (Journal of Society of Surgeons of Nepal, 2023)
Introduction: This study was done to identify the reliability of RUT in detecting H. Pylori in patients of gastritis by performing Histopathological examination. Endoscopic biopsy samples were taken from gastritis lesions present in the stomach. Methods: This was a prospective observational study done at Jawaharlal Nehru Medical College (JNMC), Aligarh Muslim University (AMU), Aligarh between May 2021 and May 2022 with a sample size of 230 patients. The endoscopists performed RUT on biopsy samples taken from gastritis lesions and sent another biopsy sample from the same patient for histopathological examination. On the basis of histopathological report, results were compared and analyzed. Results: In our study the specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of RUT were 60.81%, 67.31% ,78.36%, 46.88% , and 65.22%, respectively. Conclusion: Our study suggests that RUT can reliably identify Helicobacter pylori infection in gastric mucosa.